Clinical case of conservative treatment on the tooth with large periapical destruction - G. T. Saleeva; R. F. Mustakimova; M. I. Shamsutdinov; D. K. Sabirova; I. R. Saleeva (Эндодонтия Today)
Nowadays, sometime, the dentists unreasonably preferred surgical treatment instead of endodontic treatment. The article considers the clinical case of conservative treatment of a tooth with large periapical destruction and the results of dynamic observation.